2008
DOI: 10.3341/jkos.2008.49.4.696
|View full text |Cite
|
Sign up to set email alerts
|

Intraviteal Bevacizumab (Avastin®) Injection for the Treatment of Early-Stage Neovascular Glaucoma

Abstract: Purpose: This case is conducted to assess the short-term safety and efficacy of intravitreal bevacizumab injection in patient with early-stage of the neovascular glaucoma (NVG) without peripheral anterior synechiae. Case summary: A 66-year-old patient with a history of proliferative diabetic retinopathy presented with neovascularization of the iris and the angle and high intraocular pressure of 30 mmHg. The patient received a single injection of bevacizumab (1.25 mg /0.05 mg) intravitreally. The visual acuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 18 Some studies have reported on the short-term efficacy and safety of off-label IVB in the treatment for NVI and NVG. 9 - 11 A marked regression of NVI has been shown to occur within one to two weeks after the injection. IOP was controlled for the short follow-up period in most patients, even those with early-stage NVG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 18 Some studies have reported on the short-term efficacy and safety of off-label IVB in the treatment for NVI and NVG. 9 - 11 A marked regression of NVI has been shown to occur within one to two weeks after the injection. IOP was controlled for the short follow-up period in most patients, even those with early-stage NVG.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported on the short-term efficacy and safety of off-label IVB in the treatment for NVI and NVG 9-11. A marked regression of NVI has been shown to occur within one to two weeks after the injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regression of the iris and angle of neovascularization were confirmed from the second week after injection. 15 …”
Section: Discussionmentioning
confidence: 99%